Urban income segregation and homicides: An analysis using Brazilian cities selected by the Salurbal project - Maria Izabel dos Santos; Gervásio Ferreira dos Santos; Anderson Freitas; J. Firmino de Sousa Filho; Caio Castro; Aureliano S. Souza Paiva; Amélia A. de Lima Friche; Sharrelle Barber; Waleska Teixeira Caiaffa; Maurício L. Barreto (Elsevier, 2021)
This paper investigates the associations of income segregation with homicide mortality across 152 cities in Brazil. Despite GDP increases, an important proportion of the Brazilian population experiences poverty and extreme poverty. Segregation refers to the way that different groups are located in space based on their socioeconomic status, with groups defined based on education, unemployment, race, age, or income levels. As a measure of segregation, the dissimilarity index showed that overall, it would be necessary to relocate 29.7% of urban low-income families to make the spatial distribution of income homogeneous. For the ten most segregated cities, relocation of more than 37% of families would be necessary. Using negative binomial models, we found a positive association between segregation and homicides for Brazilian cities: one standard deviation higher segregation index was associated with a 50% higher homicide rate when we analyze all the socioeconomic context. Income segregation is potentially an important determinant of homicides, and should be considered in setting public policies.